2010
DOI: 10.1021/ml100016x
|View full text |Cite
|
Sign up to set email alerts
|

SMARTCyp: A 2D Method for Prediction of Cytochrome P450-Mediated Drug Metabolism

Abstract: SMARTCyp is an in silico method that predicts the sites of cytochrome P450-mediated metabolism of druglike molecules. The method is foremost a reactivity model, and as such, it shows a preference for predicting sites that are metabolized by the cytochrome P450 3A4 isoform. SMARTCyp predicts the site of metabolism directly from the 2D structure of a molecule, without requiring calculation of electronic properties or generation of 3D structures. This is a major advantage, because it makes SMARTCyp very fast. Oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
316
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(324 citation statements)
references
References 29 publications
4
316
0
4
Order By: Relevance
“…For prediction of the former, docking simulation using the substrate and a CYP3A4 structure is widely used. There are many methods for SOM prediction [6], including SMARTCyp [7] and MetaSite [8]. The reported methods use a set of oxidative reactivities of fragment molecules (precalculated by quantum mechanical techniques such as density functional theory [DFT]) in combination with accessibility estimation methods such as the use of topological accessibility descriptors and superimposition of substrates with binding site grids.…”
Section: Introductionmentioning
confidence: 99%
“…For prediction of the former, docking simulation using the substrate and a CYP3A4 structure is widely used. There are many methods for SOM prediction [6], including SMARTCyp [7] and MetaSite [8]. The reported methods use a set of oxidative reactivities of fragment molecules (precalculated by quantum mechanical techniques such as density functional theory [DFT]) in combination with accessibility estimation methods such as the use of topological accessibility descriptors and superimposition of substrates with binding site grids.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al performed semi-empirical QM calculations and found that the site with a hydrogen abstraction energy lower than 27 kcal mol −1 and solvent accessible surface area (SASA) greater than 8 Å would be more likely to be metabolized (Singh et al 2003). Rydberg et al developed SMARTCyp, which can predict SOM directly from the 2D structure of a molecule without 3D structure generation, and the prediction speed of this model has increased considerably (Rydberg et al 2010). In addition, SMARTCyp is based on atom reactivity and accessibility, where the reactivity can be rapidly retrieved from a pool of pre-calculated energies of fragments by SMARTS matching, and the accessibility was evaluated using the relative location of an atom in a molecule.…”
Section: Som Predictionmentioning
confidence: 99%
“…O candidato a fármaco foi submetido ao software SMARTCyp, disponível em http://smartcyp.sund.ku.dk/. Para interpretação dos resultados, quanto mais baixas as energias de ativação, mais provável que um sítio seja metabolizado (RYDBERG et al, 2010).…”
Section: Metodologia Predição Do Metabolismo Utilizando O Software Smunclassified
“…Isto se justifica devido o SMARTCyp, em contraste com MetaPrint2D-React, não depender de dados já existentes na literatura e, por isso, tem uma menor tendenciosidade nos resultados. Outra vantagem é que esse software prevê o local de metabolismo diretamente da estrutura 2D de uma molécula, sem exigir cálculo de propriedades eletrônicas ou geração de estruturas 3D (RYDBERG et al, 2010). Entretanto, o SMARTCyp não é capaz de prever os metabólitos, o que pode ser de grande importância no P&D de fármacos e, para preencher esta lacuna, foi utilizado o MetaPrint2D-React.…”
Section: Cyp2c Cyp2d6unclassified
See 1 more Smart Citation